Comparative Study of Operative Complications in Diabetic & Non-Diabetic Individuals in Adult Age Group After Laparoscopic Cholecystectomy - Elahi, Asad; Rehman, Habib Ur; Ibrahim, Hasnan; Masood, Abdullah Bin; Muneer, Muhammad Asad; Hussain, Muzammil (Biological and Clinical Sciences Research Journal, 2025)
Laparoscopic cholecystectomy (LC) is the gold standard treatment for symptomatic gallstone disease. However, diabetes mellitus (DM) is associated with an increased risk of postoperative complications, including surgical site infections (SSIs), delayed wound healing, and prolonged recovery. In Pakistan, where both gallstone disease and diabetes have a high prevalence, limited research has been conducted on the impact of diabetes on surgical outcomes following LC. This study aims to compare operative complications in diabetic and non-diabetic individuals undergoing LC in a tertiary care hospital. Methods: This prospective comparative study was conducted at the tertiary care hospital from April 2024 to September 2024. A total of 90 adult patients undergoing elective LC were enrolled and categorized into two groups: diabetics (n = 45) and non-diabetics (n = 45). Preoperative evaluation included fasting blood sugar, HbA1c, and imaging assessments. Intraoperative parameters such as operative time, bleeding, and gallbladder perforation were recorded. Postoperative complications, including SSIs, bile leakage, postoperative bleeding, hospital stay, and readmission rates, were monitored. Data were analyzed using SPSS version 26, with p<0.05 considered statistically significant. Results: Diabetic patients had significantly longer operative times (48.6 ± 10.2 minutes vs. 42.3 ± 9.5 minutes, p=0.01) and higher intraoperative blood loss compared to non-diabetics. Postoperative SSIs were more frequent in diabetics (24.4% vs. 8.9%, p=0.04), as were readmissions within 30 days (15.6% vs. 4.4%, p=0.03). The mean hospital stay was longer in diabetics (3.8 ± 1.2 days vs. 2.9 ± 0.9 days, p=0.02), and return to normal activities was delayed (10.5 ± 2.4 days vs. 7.9 ± 2.1 days, p=0.01). The overall incidence of bile leakage and postoperative bleeding was higher in diabetic patients, though not statistically significant. Conclusion: Diabetic patients undergoing LC are at a significantly higher risk of prolonged operative times, increased SSIs, longer hospital stays, and delayed recovery compared to non-diabetic individuals. These findings highlight the need for strict perioperative glycemic control, optimized surgical techniques, and extended postoperative monitoring in diabetic patients. Given the rising prevalence of diabetes in Pakistan, implementing targeted strategies to minimize perioperative complications in diabetic individuals is crucial for improving surgical outcomes.